2017
DOI: 10.1038/s41598-017-17888-9
|View full text |Cite
|
Sign up to set email alerts
|

The unfolded protein response impacts melanoma progression by enhancing FGF expression and can be antagonized by a chemical chaperone

Abstract: The mechanisms hallmarking melanoma progression are insufficiently understood. Here we studied the impact of the unfolded protein response (UPR) - a signalling cascade playing ambiguous roles in carcinogenesis - in melanoma malignancy. We identified isogenic patient-derived melanoma cell lines harboring BRAFV600E-mutations as a model system to study the role of intrinsic UPR in melanoma progression. We show that the activity of the three effector pathways of the UPR (ATF6, PERK and IRE1) was increased in metas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 48 publications
(57 reference statements)
1
16
0
2
Order By: Relevance
“…Afterwards, combined with clinical survival information, we found unfolded protein response was the most significant pathway correlated with OS of melanoma patients. Obviously, the unfolded protein response has been recognized as a crucial role in tumor progression and metastasis [ 29 , 30 ]. Numerous researches showed that unfolded protein response related genes (UPRRGs) are highly expressed in many cancers including colorectal, prostate, lung cancers, ovarian and breast [ 31 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Afterwards, combined with clinical survival information, we found unfolded protein response was the most significant pathway correlated with OS of melanoma patients. Obviously, the unfolded protein response has been recognized as a crucial role in tumor progression and metastasis [ 29 , 30 ]. Numerous researches showed that unfolded protein response related genes (UPRRGs) are highly expressed in many cancers including colorectal, prostate, lung cancers, ovarian and breast [ 31 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was previously described that BRAF inhibition is able to induce the unfolded protein response (UPR) in melanoma cells 37 . Interestingly, another study recently demonstrated that the UPR can trigger the expression of FGF1 and FGF2 in melanoma cells 38 , thus raising the possibility that the BRAF inhibition causes UPR next to senescence and thereby leads to the secretion of protective FGF1. Potential differences in UPR between different cell lines could explain why some cells are potent FGF1 inducers after BRAF/MEK inhibitor treatment (e.g., A375 cells), why others are not (e.g., M14 cells).…”
Section: Discussionmentioning
confidence: 99%
“…PERK activation also increases VEGFA expression in medulloblastoma, which favors tumor migration through an autocrine manner by interacting with its receptor VEGFR2 [160]. In melanoma, both ATF6 and PERK branches of the UPR are involved in the induction of the fibroblast growth factors FGF1/2 increasing cancer cell migration in vitro [161].…”
Section: Connections Between Upr Signaling and Tumor Cell Migrationmentioning
confidence: 99%